Rancang Bangun Sistem Informasi Ketersediaan Air Irigasi Subak Berbasis JavaScript - I Putu Arya Patrama Kharisna Putra; Ni Nyoman Sulastri; I Made Anom Sutrisna Wijaya; I Putu Gede Budisanjaya; Gusti Bagus Dwi Anugrah Harimurti (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2024)
The subak irrigation system still needs to be improved in recording and managing irrigation discharge data. Thus, an information system is required to display digital data on irrigation water discharge, which can be accessed via the website. The research aimed to d esign a responsive, flexible, and easily accessible information system, to build a live discharge data service in the form of a bar chart, and to test the features and accessibility of the information system. System design in this study was carried out in the following stages, identifying problems from the user side, designing system algorithms, integrating frameworks and API, hosting, and conducting black - box testing. The entire system design followed the waterfall model. The system has seven features: web site information , automatic discharge data from the IM - Logger tool, discharge data with manual measurements, subak news, subak gallery, login, and WhatsApp - based information features. This study tested features' responsiveness, flexibility , and system accessibility for various devices. The test results showed that all the features tested had good responsiveness and speed. In the digital data feature, irrigation discharge could be updated consistently and successfully converted into a bar chart . The system flexibility test obtained a very good score, with 100% and 93.8 % conformity percentages for wide and narrow screen devices, re spectively . In the accessibility test, 59.66% of respondents stated that the accessibility of this system was good, 39.98% was very good, and 0.6% was not good. Based on the overall results, it can be concluded that the information system functions respons ively, and flexibly , and is easily accessible